Detection of dementia and its associated risk factors among elderly population in Kuching, Sarawak - Zurraini, Binti Arabi; Syed Alwi, Bin Syed Abdul Rahman; Hii, Emily Ing Ing; Helmi, H. (2015)
Introduction: Prevalence of dementia is expected to increase with the rise in ageing population. Hence, screening for dementia in primary care is needed to identify dementia in its earlier stages. This study was conducted to screen elderly patients for dementia in primary care setting using the Mini Mental State Examination (MMSE). Methods: A cross sectional study was done on a group of elderly patients aged 60 years and above attending primary health care centers, using a systematic random sampling. Geriatric Depression Scale (GDS) was used to exclude patients with depression. The patients were then assessed with the MMSE for presence of dementia using the cut off score of 21.